Image-Based Modeling Techniques for The Creation of High-Quality Texture in Laser Scanner Model: A Case Study in Frescoed Vault - Martinez, Isabel; Zaragoza, Espejo; Caroti, Gabriella; Piemonte, Andrea (ICONARCH International Congress of Architecture and Planning, 2014)
The new survey tools used in studies aimed to preserving architectural heritage often show some dilemmas. Several studies have been able to confirm that laser scanner surveys allow to obtain three-dimensional models of high accuracy in morphology and topological level. However, nowadays the quality level of colour obtained with laser scanners is not acceptable for high quality texturing. Moreover, high quality colour medels can be obtained through techniques of Structure from Modeling, but feature a lower precision of mesh, even though results obtainable by Computer Vision programs, make this approach increasingly viable. In this context, a case study is proposed on a vault located in the Palazzo Roncioni (Pisa, Italy) decorated with a important fresco painted by the painter Giovan Battista Tempesti in the second half of the eighth century. In this case, different tests will be carried out by Structure from Modeling techniques to have a high resolution texture applied to the model obtained with laser scanner, thus obtaining a model with high resolution texture and high quality mesh. This model allows to generate an accurate documentation of the vault for digital preservation and restoration studies.